Spontaneous Polariton Currents in Periodic Lateral Chains - Nalitov, A. V. (2017)
We predict spontaneous generation of superfluid polariton currents in planar microcavities with lateral periodic modulation of both the potential and decay rate. A spontaneous breaking of spatial inversion symmetry of a polariton condensate emerges at a critical pumping, and the current direction is stochastically chosen. We analyze the stability of the current with respect to the fluctuations of the condensate. A peculiar spatial current domain structure emerges, where the current direction is switched at the domain walls, and the characteristic domain size and lifetime scale with the pumping power.